The Effect of Initial Oxygen Exposure on Diaphragm Activity in Preterm Infants at Birth - van Leuteren, Ruud W.; Scholten, Anouk W. J.; Dekker, Janneke; Martherus, Tessa; de Jongh, Frans H.; van Kaam, Anton H.; te Pas, Arjan B.; Hutten, Jeroen (Frontiers in Pediatrics, 2021)
Background The initial FiO2 that should be used for the stabilization of preterm infants in the delivery room (DR) is still a matter of debate as both hypoxia and hyperoxia should be prevented. A recent randomized controlled trial showed that preterm infants (gestational age (GA) < 30 weeks) stabilized with an initial high FiO2 (1.0) had a significantly higher breathing effort than infants stabilized with a low FiO2 (0.3). As the diaphragm is the main respiratory muscle in these infants, we aimed to describe the effects of the initial FiO2 on diaphragm activity. Methods In a subgroup of infants from the original bi-center randomized controlled trial diaphragm activity was measured with transcutaneous electromyography of the diaphragm (dEMG), using three skin electrodes that were placed directly after birth. Diaphragm activity was compared in the first five minutes after birth. From the dEMG respiratory waveform several outcome measures were determined for comparison of the groups: average peak- and tonic inspiratory activity (dEMGpeak and dEMGton respectively), inspiratory amplitude (dEMGamp¬), area under the curve (dEMGAUC) and the respiratory rate (RR). Results Thirty-one infants were included in this subgroup, of which 29 could be analyzed (n=15 (median GA 28.4 weeks) and n=14 (median GA 27.9 weeks) for the 100% and 30% oxygen group, respectively). Tonic diaphragm activity was significantly higher in the high FiO2-group (4.3 ± 2.1 µV vs. 2.9 ± 1.1 µV; p=0.047). The other dEMG-parameters (dEMGpeak, dEMGamp, dEMGAUC) showed consistently higher values in the high FiO2 group, but did not reach statistical significance. Average RR showed similar values in both groups (34 ± 9 vs. 32 ± 10 breaths/minute for the high and low oxygen group, respectively). Conclusion Preterm infants stabilized with an initial high FiO2 showed significantly more tonic diaphragm activity and an overall trend towards a higher level of diaphragm activity than those stabilized with an initial low FiO2. These results confirm that a high initial FiO2 after birth stimulates breathing effort, which can be objectified with dEMG.